(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
We present and compare the results of permanent electric dipole moments (EDMs) of various closed-shell atoms due to the nuclear Schiff moment (NSM) and the tensor-pseudotensor (T-PT) interactions between the atomic nuclei and electrons. In order to highlight the role of electron-correlation effects in obtaining accurate EDM results, we employ a number of relativistic many-body methods including coupled-cluster theory at different degrees of approximation. On combining our results obtained from the relativistic coupled-cluster (RCC) at the levels of singles and doubles excitations (CCSD method) with the available EDM measurements we obtain accurate bounds on the couplings \(S\) and \(C_T\) associated with the respective NSM and T-PT interactions. The most precise EDM measurement on \(^199\)Hg in combination with our CC results yield limits on the above couplings as \(S<1.45 × 10^-12|e|\)fm\(^3\) and \(C_T < 2.09 × 10^-9\) respectively. Further combining these bounds with the latest nuclear structure and quantum chromodynamics calculations we infer limits on the strong CP-violating parameter and for the combined up- and down- quark chromo-EDMs as \(|θ| < 1.1 × 10^-9\) and \(|d_u - d_d| < 2.8 × 10^-26 |e|\)cm, respectively.